2019
DOI: 10.1111/tpj.14412
|View full text |Cite
|
Sign up to set email alerts
|

Rosa hybrida RhERF1 and RhERF4 mediate ethylene‐ and auxin‐regulated petal abscission by influencing pectin degradation

Abstract: cn). † These authors contributed equally to this work. SUMMARYThe timing of plant organ abscission is modulated by the balance of two hormones, ethylene and auxin, while the mechanism of organ shedding depends on the loss of middle lamella pectin in the abscission zone (AZ). However, the mechanisms involved in sensing the balance of auxin and ethylene and that affect pectin degradation during abscission are not well understood. In this study, we identified two members of the APETALA2/ethylene-responsive factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 60 publications
2
44
2
Order By: Relevance
“…During the plant organ abscission, a large number of transcription factors are also involved. Including ERF family [49], ARF family [13], MADS-box family [65,66], and HD-ZIP family [16,67]. In the present study, ERF and MADS-box did not accumulate, However, two HD-ZIP family proteins were significantly up-regulated.…”
Section: Transcription Factor Raleted Abscissioncontrasting
confidence: 48%
See 1 more Smart Citation
“…During the plant organ abscission, a large number of transcription factors are also involved. Including ERF family [49], ARF family [13], MADS-box family [65,66], and HD-ZIP family [16,67]. In the present study, ERF and MADS-box did not accumulate, However, two HD-ZIP family proteins were significantly up-regulated.…”
Section: Transcription Factor Raleted Abscissioncontrasting
confidence: 48%
“…Our proteomics profiling of sweet cherry abscising carpopodium showed bidirectional changes in the expression of the cell wall-related proteins, probably associated not only with the ongoing process of abscission but also with the progressive development of the organs that are not dropped (Table S4). However, it is worth noting that most of the enzymes involved in cell wall degradation showed a trend of up-regulation, including cellulose [3], pectinase [47], polygalacturonase [48], β-galactosidase [49], which play a major role in cell wall degradation. Moreover, the enzymatic activity of cellulose, pectinase and polygalacturonase were significantly higher than non-abscising carpopodium (Figure 2a).…”
Section: Cell Wall Metabolism and Abscissionmentioning
confidence: 99%
“…Thus, for example, excess ethylene accumulation were observed in tomato and maize mutants characterized by an ABA de cit [41,42]. Contrastingly, ETH and IAA are well-known pivotal effectors of plant organ abscission, and have been shown to act antagonistically to control organ abscission [43]. In this study, pro ling of global gene expressions in AZ revealed DEGs involved in IAA, ETH, and GA pathways ( Table 1, Table S3).…”
Section: Discussionmentioning
confidence: 64%
“…The dual-luciferase reporter assay was conducted using the dual-luciferase reporter assay systems (Promega, Madison, WI, USA) and D-luciferin (Promega) as previously described (Gao et al, 2019). The LUC images were taken using an ikon-L936 imaging system (Andor Tech, Belfast, UK).…”
Section: Dual-luciferase Reporter Assay In N Benthamianamentioning
confidence: 99%